Preparation of an Antioxidant Assembly Based on a Copolymacrolactone Structure and Erythritol following an Eco-Friendly Strategy - Aurica P. Chiriac; Alina Ghilan; Alexandru-Mihail Serban; Ana-Maria Macsim; Alexandra Bargan; Florica Doroftei; Vlad Mihai Chiriac; Loredana Elena Nita; Alina Gabriela Rusu; Andreea-Isabela Sandu (MDPI AG, 2022)
The study presents the achievement of a new assembly with antioxidant behaviour based on a copolymacrolactone structure that encapsulates erythritol (Eryt). Poly(ethylene brassylate-co-squaric acid) (PEBSA) was synthesised in environmentally friendly conditions, respectively, through a process in suspension in water by opening the cycle of ethylene brassylate macrolactone, followed by condensation with squaric acid. The compound synthesised in suspension was characterised by comparison with the polymer obtained by polymerisation in solution. The investigations revealed that, with the exception of the molecular masses, the compounds generated by the two synthetic procedures present similar properties, including good thermal stability, with a Tpeak of 456 °C, and the capacity for network formation. In addition, the investigation by dynamic light scattering techniques evidenced a mean diameter for PEBSA particles of around 596 nm and a zeta potential of −25 mV, which attests to their stability. The bio-based copolymacrolactone was used as a matrix for erythritol encapsulation. The new PEBSA-Eryt compound presented an increased sorption/desorption process, compared with the PEBSA matrix, and a crystalline morphology confirmed by X-ray diffraction analysis. The bioactive compound was also characterised in terms of its biocompatibility and antioxidant behaviour.